Vasa praevia: a case report and literature review - Norvilaitė, Kristina; Peštenytė, Aurelija; Bužinskienė, Diana; Drąsutienė, Gražina; Arlauskienė, Audronė; Poškus, Tomas; Ostapenko, Andrej (Acta medica Lituanica, 2016)
Background. The aim of this article is to present a rare clinical case of vasa praevia as well as to assess the relevance of the problem by reviewing the latest literature sources. Materials and methods. In this report we present a case of a 33-yearold woman diagnosed with vasa praevia at 33 weeks of pregnancy, after hospitalisation with preterm rupture of membranes following the delivery of a  live healthy baby through a  lower segment Caesarean section during 33rd week of gestation at Vilnius University Hospital Santariškių Clinics. We investigated all the documentation of the patient before and after delivery. Results and conclusions. Vasa praevia is a  rather rare pathology which is likely to occur during pregnancy, may result in heavy bleeding and be particularly threatening to the  fetus life. A  timely diagnosis for these women is essential. The gold standard for vasa praevia diagnosis is the fetal ultrasound scan. Vasa praevia pathology is found during the routine second trimester ultrasound check-up. The selection of proper tactics applied during pregnancy care is essential. At the gestational age of 28–32, it is advisable to mature fetal lungs as well as the fetus condition should be investigated by a perinatologist. The mode of delivery is the C-section which tends to reduce the frequency of possible complications.